If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 = 3x + 8 Reorder the terms: -5 = 8 + 3x Solving -5 = 8 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -5 + -3x = 8 + 3x + -3x Combine like terms: 3x + -3x = 0 -5 + -3x = 8 + 0 -5 + -3x = 8 Add '5' to each side of the equation. -5 + 5 + -3x = 8 + 5 Combine like terms: -5 + 5 = 0 0 + -3x = 8 + 5 -3x = 8 + 5 Combine like terms: 8 + 5 = 13 -3x = 13 Divide each side by '-3'. x = -4.333333333 Simplifying x = -4.333333333
| -4x+8=-12+x-8-7 | | -(4x-10)+2(3x+15)= | | 4x^3+24x^2+12x-40=0 | | 6x-3y+14w-5y-4w+9x= | | 592=2L+2(5L+6) | | 2(-1)+9= | | 12x+9=9x-18 | | 4x-5=3-7x | | 48=4(x+10) | | 4u^2-4=15 | | 5v+7=6v-11 | | 6x=5x+16 | | 16(x+3)-4x=4(3x+2)-12 | | 5(3x-7)-(3x+9)= | | 19-u=238 | | -8(b-5)=-2(b+1) | | a-3[b-2(c-x)]=4 | | 167=2(3w-5)+2w | | 3x+6=9(x+4) | | 3(6p+5)=21 | | 3x+6=9(x+9) | | 7(4x+7)=6(1+x)-1 | | 2e^3x-2=7 | | C-13=5(3) | | 40=8(n-2) | | -5(8x+4)=-140 | | c=49.99-.25*49.99 | | 4[8-(-9x-1)]=180x+52 | | 3y-10x=-45 | | 5(4x-3)=15 | | x=(4y-9)(6y-7) | | 5+x=4(8) |